Follow-up pathways for alcohol use disorders patients: A naturalistic study in a tertiary care center in south India - Soyuz John; M Somashekar Vidyashree; Samir Kumar Praharaj (Indian Journal of Psychiatry)
Background: Understanding the sequences of patient contacts, visit patterns to treatment centers, reasons for dropout, and outcomes following treatment discontinuation is the crucial for planning treatment and aftercare for patients with alcohol use disorder (AUD). Aim: To examine the follow-up pathways of patients with AUD. Materials and Methods: A pathway-to-care study was conducted in 2021 among 110 patients with AUD. The same cohort was followed-up in 2024, 3 years later. Data were collected through reviews of psychiatry files, hospital electronic medical records, and phone interviews with patients or their relatives. The modified the World Health Organization (WHO) Encounter form and a structured interview schedule were used for data collection. Results: The overall dropout rate without a single follow-up visit was 49%. Twenty-eight percent of patients returned to the psychiatry department at least once, but only 8% continued treatment, while the rest dropped out within 3 years. The highest initial dropout rate (59.3%) was observed among patients, who accessed treatment through other hospital departments, with only 14.8% returning for follow-up in psychiatry. However, over 50% of patients who first visited the psychiatry department directly returned for follow-up. Conclusion: The initial dropout rate was notably high, especially among patients referred from other hospital departments. Strengthening treatment strategies for these patients and improving follow-up services may lead to the better retention and higher abstinence rates.